(untitled) (Fiep Bulletin - online, 2019)
Aging and sedentary lifestyle leads to a progressive loss of functional abilities, triggering emotional and psychicconflicts that profoundly diminish the quality of life. Ballroom dancing is among one of the physical exercises practiced by theelderly public, which provides several benefits in the conditions for the improvement of the quality of life. Thus, the present studyaims to evaluate the quality of life of elderly women practicing ballroom dancing. The sample consisted of ten elderly womenparticipating in dance classes in the extension project: Age with Quality in the city of Vitória de Santo Antão / PE. A questionnaireon the WHOQOL-BREF abbreviated version was used (for the Likert scale analysis of general quality of life, satisfaction withone’s own health and the four domains: physical, psychological, social relations and the environment environment). In the resultsof the present study, the values prevailed as regular and show the potential that hall dance has in contributing to the improvementand maintenance of the QoL of the elderly. It is suggested that more studies be developed in this theme, fostering the importanceof ballroom dancing in the QOL of the elderly.